2014
DOI: 10.1016/j.yexcr.2014.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Uric acid inhibition of dipeptidyl peptidase IV in vitro is dependent on the intracellular formation of triuret

Abstract: Uric acid affects endothelial and adipose cell function and has been linked to diseases such as hypertension, metabolic syndrome, and cardiovascular disease. Interestingly uric acid has been shown to increase endothelial progenitor cell (EPC) mobilization, a potential mechanism to repair endothelial injury. Since EPC mobilization is dependent on activity of the enzyme CD26/dipeptidyl peptidase (DPP)IV, we examined the effect uric acid has on CD26/DPPIV activity. Uric acid inhibited the CD26/DPPIV associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
2
2
0
Order By: Relevance
“…Previous reports demonstrate a critical role for oxidants in stimulating NFAT5 transcriptional activity (31,32). In this regard, uric acid, despite being an important antioxidant in the systemic circulation, can also act as a prooxidant molecule intracellularly (9,33). Consistently, and as shown in Fig.…”
Section: Regulation Of Aldose Reductase By Uric Acid-dependent Oxidatsupporting
confidence: 80%
“…Previous reports demonstrate a critical role for oxidants in stimulating NFAT5 transcriptional activity (31,32). In this regard, uric acid, despite being an important antioxidant in the systemic circulation, can also act as a prooxidant molecule intracellularly (9,33). Consistently, and as shown in Fig.…”
Section: Regulation Of Aldose Reductase By Uric Acid-dependent Oxidatsupporting
confidence: 80%
“…However, it is well recognized that hyperuricemia is associated with metabolic diseases and endothelial dysfunction. Consistent with our observed association between variation in DPP4 polymorphisms and hyperuricemia, Mohandas et al demonstrated that uric acid inhibits DPP4 activity when it is anchored to the membrane and that the inhibitory effect depends on the redox state of cells and formation of intracellular triuret [58].…”
Section: Discussionsupporting
confidence: 91%
“…We reported an association of the rs12617336 minor allele with a high risk of hyperuricemia. The relationship between the uric acid and DPP4 was established by Mohandas et al, who demonstrated that uric acid inhibits DPP4 activity when it is anchored to the membrane and that the inhibitory effect depends on the redox state of cells and the formation of intracellular triuret (Mohandas et al, 2014).…”
Section: Discussionmentioning
confidence: 99%